PROBLEMATICS OF SCIENCE EDUCATION: HUMAN RESOURCES, TEACHERS AND PROSPECTIVE TEACHERS - Boroallo, Paramitha Yemima; Sulviana; Oktavia, Rini; Ningsih, Purnama (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2025)
This study explores how important educational resources and infrastructure are to raising the calibre and efficacy of science instruction. It highlights how crucial physical resources like laboratories and learning tools, as well as digital media like eBooks and instructional videos, are to creating a vibrant and engaging learning environment. Notwithstanding the possible advantages, the research points to several important obstacles, such as insufficient funding, a lack of standardized equipment, restricted resource availability, and a lack of teacher preparation in technology integration. To address these issues, a thorough strategy is suggested, emphasizing continual professional development for teachers and matching curriculum requirements with available resources. The results show that to guarantee fair access to educational resources and enhance the results of science education, stakeholders must work together and have strong policy support.